Análisis de estrategias para el escalamiento de un fotobiorreactor tipo Airlift para el cultivo de microalgas (2021)
The objective of this research project is to present the most appropriate strategy for scaling up an airlift-type photobioreactor, since, as is known, it is still a challenge. For the development of this, the literature review methodology was implemented, so that the microalgae cultivation parameters were specified, such as the temperature where values ​​are established in a range of 27 ° C to 35 ° C, the pH between 8.2 to 8.7, light intensity 130,000 lux to 270,000 lux, agitation between the values ​​0.1 to 0.3 vvm, also identifying the most suitable type of culture for the microalgae, the cultivation being the most consistent